Relationship between Biofilm Formation and Antibiotic Resistance and Adherence Genes in Staphylococcus aureus Strains Isolated from Raw Cow Milk in Shahrekord, Iran - Pajohesh, Rasul; Tajbakhsh, Elahe; Momtaz, Hassan; Rahimi, Ebrahim (International Journal of Microbiology, 2022)
The production of biofilms by S. aureus contributes significantly to treatment failures. The present study aims to establish the relationship between biofilm formation and antibiotic resistance and adhesion genes in Staphylococcus aureus strains isolated from raw cow milk in Shahrekord, Iran. A total of 90 samples of raw cow’s milk were collected. Presumptive S. aureus strains were obtained using Baird-Parker plates after enrichment in tryptone soy broth, and final colonies were selected from brain heart infusion. Additional tests such as coagulase were done, and the identification was confirmed by the detection of the aroA gene. Biofilm producing strains were screened using a spectrophotometry method applied to microplates. Crystal violet staining was used to quantify the formation of biofilm. An antibiotic susceptibility test was performed using the Kirby–Bauer disc diffusion method. PCR was used to detect several biofilm and antibiotics resistance related genes. The chi-square test and Fisher’s exact test were used to establish a statistically significant relationship between biofilm reaction and antibiotic resistance (p value <0.05). Results show a moderate (38.88%) recovery rate of S. aureus in milk and 65.71% of the isolates were strong biofilm producers. Antibiotic susceptibility tests show an alarming rate of resistance to beta-lactam antibiotics, especially penicillin (100%), ampicillin (91.42%), and oxacillin (71.42%). This finding correlates with antibiotic resistance gene detection, in which the gene blaZ was most found (71.42%), followed by mecA and Aac-D (42.85%). Detection of biofilm-related genes shows that all the genes targeted were found among S. aureus isolates. Statistical tests show a significant correlation between biofilm production and antibiotic resistance in S. aureus. This study revealed that there is a significant correlation between biofilm production and antibiotic resistance in S. aureus isolated from raw milk. These results highlight the need for regular surveillance of the occurrence of S. aureus strains in milk and milk products in Iran.